Shock waves in microchannels. (29th April 2013) - Mirshekari, G.; Brouillette, M.; Giordano, J.; Hébert, C.; Parisse, J.-D.; Perrier, P.
Abstract: A fully instrumented microscale shock tube, believed to be the smallest to date, has been fabricated and tested. This facility is used to study the transmission of a shock wave, produced in a large (37 mm) shock tube, into a 34 μ m hydraulic diameter and 2 mm long microchannel. Pressure microsensors of a novel design, with gigahertz bandwidth, are used to obtain pressure–time histories of the microchannel shock wave at five axial stations. In all cases the transmitted shock wave is found to be weaker than the incident shock wave, and is observed to decay both in pressure and velocity as it propagates down the microchannel. These results are compared with various analytical and numerical models, and the best agreement is obtained with a Navier–Stokes computational fluid dynamics computation, which assumes a no-slip isothermal wall boundary condition; good agreement is also obtained with a simple shock tube laminar boundary layer model. It is also found that the flow developing within the microchannel is highly dependent on conditions at the microchannel entrance, which control the mass flux entering into the device. Regardless of the micrometre dimensions of the present facility, shock wave propagation in a microchannel of that scale exhibits a behaviour similar to that observed in large-scale facilities operated at low pressures, and the shock attenuation can be explained in terms of accepted laminar boundary models.